2010
DOI: 10.1016/j.cryobiol.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and ascorbic acid prevent DNA damage induced by cryopreservation in human semen

Abstract: Cryopreservation of human semen can cause DNA damages, which compromise the fertilization and normal embryo development. The present study showed that the antioxidant resveratrol prevents these damages both in fertile and infertile men. The addition of ascorbic acid before cryopreservation can reduce DNA damages only in infertile men. Although further studies are needed, the present work showed that resveratrol could be considered in human cryopreservation procedures to avoid/minimize DNA damages and preserve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 6 publications
5
67
0
5
Order By: Relevance
“…For sperm cryopreservation, several factors, such as the pre-frozen sperm quality baseline, freezing and thawing method, and cryopreservative medium, and volume of cryopreserved specimen, have been previously demonstrated to be the crucial factors relating to post-thawing sperm outcome [2,7,21,23,24]. Several attempts have been made to improve cryopreservation techniques and media, leading to the improvement of cryopreservation [6,21,22,25]. Notably, the quality of ejaculated semen is also related to the outcome of cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For sperm cryopreservation, several factors, such as the pre-frozen sperm quality baseline, freezing and thawing method, and cryopreservative medium, and volume of cryopreserved specimen, have been previously demonstrated to be the crucial factors relating to post-thawing sperm outcome [2,7,21,23,24]. Several attempts have been made to improve cryopreservation techniques and media, leading to the improvement of cryopreservation [6,21,22,25]. Notably, the quality of ejaculated semen is also related to the outcome of cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dead spermatozoa or leukocytes in pre-freezing semen detrimentally affect the sperm survival rate and the fertility potential after thawing through the ROS generation process [6]. A number of studies have demonstrated that supplemental addition of antioxidative to cryoprotective medium, e.g., ascorbate or catalase, minimize DNA damage and preserve sperm integrity; however, the benefit of these supplementations is still debated [25,26]. In this study, we hypothesized that sperm preparation before freezing, compared with sperm preparation after freezing-thawing, would improve post-thawed sperm, i.e., sperm motility, sperm vitality and non-apoptotic sperm.…”
Section: Introductionmentioning
confidence: 99%
“…107,108 Several studies have also examined the role of antioxidants in protecting sperm DNA from injury following cryopreservation and thawing. Most studies have shown that antioxidants (vitamin C, catalase, resveratrol and genistein) can protect the sperm DNA from oxidative injury during cryopreservation and subsequent thawing [109][110][111][112] ( Table 6). In contrast, Taylor et al reported that the antioxidant vitamin E does not protect sperm DNA during cryopreservation.…”
Section: Role Of In Vitro Antioxidants In Protecting Spermatozoa Frommentioning
confidence: 99%
“…Therefore, protecting the spermatozoa from cryopreservation-induced DNA damage and loss of sperm functional competence is clinically relevant in assisted reproductive technology (ART). Taking this into consideration, the most common approach followed hitherto, was to protect the sperm DNA during freeze-thaw process by using free radical scavengers along with the cryopreservation medium [12,13].…”
Section: Introductionmentioning
confidence: 99%